2016
DOI: 10.1186/s12884-016-1122-6
|View full text |Cite|
|
Sign up to set email alerts
|

Increasing prevalence and incidence of domestic violence during the pregnancy and one and a half year postpartum, as well as risk factors: -a longitudinal cohort study in Southern Sweden

Abstract: BackgroundDomestic violence is a global health problem as well as a violation against human rights. The aim of this study was to explore prevalence and incidence of domestic violence during pregnancy and 1 to 1.5 years postpartum as well as to explore the history of violence among new mothers in the southwestern region of Sweden. In addition, the aim was to explore the association between domestic violence postpartum and possible risk factors.MethodsThis is a longitudinal cohort-study including pregnant women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
4
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 38 publications
8
56
4
7
Order By: Relevance
“…The numbers are comparable with a new longitudinal cohort study done in Sweden [9]. Among 1573 women in this study, 2.5% reported violence during pregnancy [9]. The prevalence increased in the early postnatal period to 3.3% [9].…”
Section: Introductionsupporting
confidence: 86%
“…The numbers are comparable with a new longitudinal cohort study done in Sweden [9]. Among 1573 women in this study, 2.5% reported violence during pregnancy [9]. The prevalence increased in the early postnatal period to 3.3% [9].…”
Section: Introductionsupporting
confidence: 86%
“…The study used a longitudinal design and is part of a previous published project 'Pregnant women and new mothers' health and life experience, with 'life experience' which also included collecting data around intimate partner violence [3,18,19]. Included participants were primigravida and multiparous women ≥18 years of age, receiving antenatal care (ANC), and who could read and write in Swedish or English.…”
Section: Methodsmentioning
confidence: 99%
“…In Europe, 20% of pregnant women experienced IPV from a current partner with 42% of the women reporting IPV from a previous partner [17]. Whereas in Sweden, recent results from a longitudinal cohort study completed in southwest Sweden revealed a DV prevalence rate of 2.5% of the pregnant population [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…pregnancy has been associated with adverse pregnancy outcomes, such as low birth weight, premature labour, preterm delivery, miscarriage, and foetal injury [25]. In developed countries as Sweden the prevalence of domestic violence during pregnancy, irrespective of type or severity was reported by 2.5% [26]. In North America, most estimates of prevalence of such violence fall between 4% and 8% [27].…”
Section: Discussionmentioning
confidence: 99%